Feedlot performance, feeding behavior and rumen morphometrics of Nellore cattle submitted to different feeding frequencies (Scientia Agricola, 2018)
Owing to the lack of information in the literature about the ideal feeding frequency adopted by feedlot systems, this study was designed to evaluate the effect of different feeding frequencies on performance, carcass traits, feeding behavior and rumen morphometrics of Nellore cattle. Forty-eight yearling bulls were housed in individual pens with an average initial body weight of 358.2 kg. The experiment was designed as a completely randomized block and the treatments were the feeding of cattle one, two, three, or four times daily (n = 12 per treatment). Orthogonal contrasts were used to assess linear, quadratic and cubic relationship between feeding frequency and the dependent variable. As feeding frequency increased, final body weight (p = 0.03) and average daily gain (p = 0.01; one: 0.98 kg d–1; two: 0.96 kg d–1; three: 1.18 kg d–1; four: 1.14 kg d–1) increased linearly and the feed:gain ratio decreased (p = 0.02). Also, as feeding frequency increased, hot carcass weight was affected cubically (p = 0.01; one: 246.9 kg; two: 243.0 kg; three: 263.1 kg; four: 258.1 kg). During the adaptation period dry matter intake variation was affected cubically (p ≤ 0.05; one: 16 %; two: 23 %; three: 14 %; four: 16 %). Increases in feeding frequency affected papillae height (p < 0.01) and papillae surface area (p < 0.01) cubically, as well as producing increases in the mitotic index (p = 0.05; one: 9 %; two: 11 %; three: 13 %; four: 13 %) and cells in proliferation (p = 0.05) linearly. Thus, Nellore yearling bulls should be fed three times daily in feedlot operations.